Improved mechanical performances of short aramid fiber‐reinforced polypropylene composites by Ti3C2 Mxene nanosheets. Issue 4 (20th January 2021) - Tang, Bolin; Yang, Yaru; Shi, Yicheng; Nie, Huijie; Xia, Hongqin; Shen, Xiaojun
Abstract: Fiber‐reinforced polypropylene (PP) composites are widely used for structural bearing because of their excellent mechanical property. So, it is necessary to improve the mechanical property of fiber‐reinforced PP composites. In this present, two‐dimensional Ti3 C2 Mxene nanosheets were bound to short aramid fiber (SAF), forming Ti3 C2 nanosheets‐modified SAF (Ti3 C2 /SAF), aiming to improve PP mechanical property. The Ti3 C2 nanosheets were obtained after hydrofluoric acid etching and ultrasonically delamination procedure, followed by chemically bound to the surface of H3 PO4 solution‐treated SAF to form Ti3 C2 /SAF. The Ti3 C2 /SAF‐reinforced PP (Ti3 C2 /SAF/PP) composites were prepared by a melt blending method. Scanning electron microscopy images showed that the Ti3 C2 /SAF modified with different concentration of Ti3 C2 nanosheets solution presented the distinct morphologies, with the 0.3 mg/ml Ti3 C2 /SAF formed a relatively uniform Ti3 C2 nanosheets coating on the SAF surface. Test results of mechanical performance indicated that the tensile and impact strength of Ti3 C2 /SAF/PP composites were significantly improved. Especially, the maximum tensile and impact strength of 0.3 Ti3 C2 /SAF/PP composite at 5 wt% reached to 37.8 MPa and 14.0 kJ/m 2, which was increased by 11.5% (or 28.1%) in tensile strength and 12.9% (or 38.6%) in impact strength, compared with that of SAF/PP composite (or PP matrix). This can be attributed that Ti3 C2 nanosheets binding to SAF improved the interfacial bonding strength between SAF and PP. This work provides a promising strategy for improving the mechanical properties of fiber‐reinforced PP composites. Abstract : 1. Ti3 C2 nanosheets‐modified short aramid fiber were prepared through the immersion of short aramid fiber into Ti3 C2 nanosheets solution, and the Ti3 C2 /short aramid fiber‐reinforced polypropylene composites were fabricated by blending of the Ti3 C2 ‐modified short aramid fibers and polypropylene. 2. Tensile and impact strength of the polypropylene composites were effectively improved, and reached to the maximum value at 5 wt% content. 3. The improved tensile and impact strength of polypropylene composites were ascribed to the improved interfacial bonding strength between modified fibers and polypropylene.